Prediction of passive and active drag in swimming - Webb, A.; Banks, J.; Phillips, C.; Hudson, D.; Taunton, D.; Turnock, S. (Procedia Engineering, 2011)
In order to understand the physical origin of passive resistance in swimming the resistance breakdown for a swimmer is investigated. A combination of empirical methods and theoretical analysis is used to predict passive resistance in the speed range 0 - 2 m/s and is shown to provide similar results to those from experimental testing. Typical magnitudes of wave, viscous pressure and skin friction resistance contribute 59%, 33% and 8% of total passive resistance respectively at free swim speed. A comparison is made between the widely used Velocity Perturbation Method and a Naval Architecture based approach in predicting active drag. For the swimmer investigated the two approaches predict active drag of 131.4 N and 133.9 N for a swimming speed of 1.53 m/s. However, the results predicted from the Velocity Perturbation Method have a much higher uncertainty and the Naval Architecture based approach is suggested as a more robust method of predicting active drag.